Word Usage Change and the Pandemic: A Computational Analysis of Short-Term Usage Change in the Italian Reddit Community - Edoardo Signoroni; Elisabetta Jezek; Rachele Sprugnoli (IJCoL)
The COVID-19 pandemic has affected every aspect of our lives. Our work assesses whether it has also impacted the usage of the Italian language, particularly its lexicon. We create a new corpus of Italian texts taken from Reddit and apply a recent unsupervised usage change detection method on two sub-corpora, one with data from 2019 and one with data from 2020. The focus of our investigation is short-term usage change. The results for the first 10-top candidates and for a selection of candidates among the top-100 are analyzed, to show that usage change has indeed happened.